2020
DOI: 10.3389/fphar.2020.534775
|View full text |Cite
|
Sign up to set email alerts
|

Fluorofenidone Alleviates Renal Fibrosis by Inhibiting Necroptosis Through RIPK3/MLKL Pathway

Abstract: Cell death and sterile inflammation are major mechanisms of renal fibrosis, which eventually develop into end-stage renal disease. “Necroptosis” is a type of caspase-independent regulated cell death, and sterile inflammatory response caused by tissue injury is strongly related to necrosis. Fluorofenidone (AKF-PD) is a novel compound shown to ameliorate renal fibrosis and associated inflammation. We investigated whether AKF-PD could alleviate renal fibrosis by inhibiting necroptosis. Unilateral ureteral obstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Hence, fluorofenidone (AKFPD), a novel pyridone agent with similar chemical structure to PFD, was screened by our group. According to previous studies, AKFPD and PFD showed similar capacity in the aspects of anti-inflammation, anti-oxidation, and anti-fibrosis (Dai et al, 2020;Jiang et al, 2019;Meng et al, 2012;Song et al, 2016;Tang et al, 2015;Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 62%
“…Hence, fluorofenidone (AKFPD), a novel pyridone agent with similar chemical structure to PFD, was screened by our group. According to previous studies, AKFPD and PFD showed similar capacity in the aspects of anti-inflammation, anti-oxidation, and anti-fibrosis (Dai et al, 2020;Jiang et al, 2019;Meng et al, 2012;Song et al, 2016;Tang et al, 2015;Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 62%
“…Thus, Wnt/β-catenin/GSK signaling is involved in the development of renal fibrosis in acute kidney injury (Pan et al, 2021) and diabetic nephropathy (Chang et al, 2018). In our model of UUO, the pathogenesis of renal fibrosis involves a complex network orchestrated by necroptosis, oxidative stress, inflammation, TGF-β1, and activation of Wnt/catenin signaling (Jiang et al, 2015;Dai et al, 2020;Jin et al, 2020). Inhibition of necroptosis or Wnt/catenin signaling alleviates UUO-induced renal fibrosis (Xiao et al, 2017;Gong et al, 2021), implying a relationship between necroptosis and Wnt/ β-catenin signaling.…”
Section: Discussionmentioning
confidence: 90%
“…Unfortunately, there is still lack of effective therapeutic medicine. As the me-better drug of pirfenidone, fluorofenidone has a higher no observed adverse effect level (NOAEL) and longer half-time period than pirfenidone and has shown obviously anti-fibrosis effects ( Song et al, 2016 ; Dai et al, 2020 ; Tu et al, 2021 ). In the present study, we not only proved that fluorofenidone could efficiently protect ALI for the first time but also demonstrated that fluorofenidone could provide preventive and therapeutic effects for ALI.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorofenidone [1-(3-fluorophenyl)-5-methyl-2-([1H])-pyridone; AKFPD] is a novel pyridone anti-fibrosis compound which has demonstrated a remarkable therapeutic effect on organ fibrosis, including the kidney, liver, and lungs ( Song et al, 2016 ; Dai et al, 2020 ; Tu et al, 2021 ). Currently, fluorofenidone is undergoing phase II clinical trial for liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%